2003
DOI: 10.1016/j.nima.2003.08.066
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence and imaging with gas electron multipliers

Abstract: Although the GEM has been mainly used as a gaseous preamplifier device, it has been shown that using suitable gaseous mixtures the avalanches emit a large number of photons, in the UV, visible and/or NIR bands. This scintillation, readout by CCDs, has been used recently for the development of imaging detectors to be used with X-rays, alpha particles and neutrons. The luminescence process in the GEM and a summary of its applications will be presented. The latest developments, including the operation of the GEMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 25 publications
(20 reference statements)
0
20
0
Order By: Relevance
“…The light path is enclosed in a light-tight shielding. The Texas Instruments TC-241 CCD sensor with a quantum efficiency of 62% at 650 nm is well matched to the emission spectrum of Ar/CF 4 gas mixture [30]. The sensor has 375 Â 241 pixels with dimensions of 23 Â 27 mm 2 .…”
Section: Detector Designmentioning
confidence: 99%
“…The light path is enclosed in a light-tight shielding. The Texas Instruments TC-241 CCD sensor with a quantum efficiency of 62% at 650 nm is well matched to the emission spectrum of Ar/CF 4 gas mixture [30]. The sensor has 375 Â 241 pixels with dimensions of 23 Â 27 mm 2 .…”
Section: Detector Designmentioning
confidence: 99%
“…An optically transparent collecting grid was placed 3 mm away from the final GEM, thereby defining the induction gap. The 10 Â 10 cm 2 GEMs had 80 mm metal diameter holes and 70 mm bi-conical kapton holes. The kapton thickness was 50 mm and the pitch was 140 mm for all GEMs.…”
Section: The Experimental Set-upmentioning
confidence: 99%
“…It has been shown that when operated with adequate gas mixtures, the gas electron multiplier (GEM [1]) scintillation can be used for track imaging using integrating devices (CCDs) and photomultipliers [2,3]. In the last work, it was also shown that the light signals taken from a photomultiplier were faster than the charge signals and that their rise time was correlated with the track orientation, suggesting its use for the determination of the track angle in TPCs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CF 4 is a fascinating gas scintillator, i.e., its emission spectrum ranges from the far-ultraviolet to the nearinfrared with a significant fraction in the visible region [10][11][12]. It has been reported that the secondary emission spectra from CF 4 based noble gas mixtures, e.g., ArþCF 4 or HeþCF 4 , are similar to that of pure CF 4 under X-ray and electron excitation in MicroPattern Gas Detectors (MPGDs) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%